Poor Speech Perception Is Not a Core Deficit of Childhood Apraxia of Speech: Preliminary Findings. - Zuk, Jennifer; Iuzzini-Seigel, Jenya; Cabbage, Kathryn; Green, Jordan R.; Hogan, Tiffany P. (Journal of Speech, Language & Hearing Research, 2018)
Purpose: Childhood apraxia of speech (CAS) is hypothesized to arise from deficits in speech motor planning and programming, but the influence of abnormal speech perception in CAS on these processes is debated. This study examined speech perception abilities among children with CAS with and without language impairment compared to those with language impairment, speech delay, and typically developing peers. Method: Speech perception was measured by discrimination of synthesized speech syllable continua that varied in frequency (/da/-/ga/). Groups were classified by performance on speech and language assessments and compared on syllable discrimination thresholds. Within-group variability was also evaluated. Results: Children with CAS without language impairment did not significantly differ in syllable discrimination compared to typically developing peers. In contrast, those with CAS and language impairment showed significantly poorer syllable discrimination abilities compared to children with CAS only and typically developing peers. Children with speech delay and language impairment also showed significantly poorer discrimination abilities, with appreciable within-group variability. Conclusions: These findings suggest that speech perception deficits are not a core feature of CAS but rather occur with co-occurring language impairment in a subset of children with CAS. This study establishes the significance of accounting for language ability in children with CAS.